Molecular testing of raspberry plants infected with tomato black ring virus - Andersson, Alexandra (2010)
Nematode-transmitted plant viruses (such as nepoviruses) cause great economically losses in commercially important plants such as tomatoes, grapevines and raspberries all over the world. To avoid spread of the viruses the interest in mapping the viruses has increased. One of the important nepoviruses infecting European red raspberries (Rubus idaeus) is Tomato black ring virus (TBRV). TBRV has earlier been confirmed in raspberry samples from Belarus by ELISA and the aim of this bachelor degree project was to confirm these results by amplifying, cloning and sequencing the coat protein (CP) gene of the virus.